Evaluating different cost-benefit analysis methods for port security operations - Sherman, Galina; Siebers, Peer-Olaf; Menachof, David; Aickelin, Uwe (CRC Press, 2012)
Service industries, such as ports, are attentive to their standards, a smooth service flow and economic viability. Cost benefit analysis has proven itself as a useful tool to support this type of decision making; it has been used by businesses and governmental agencies for many years. In this book chapter we demonstrate different modelling methods that are used for estimating input factors required for conducting cost benefit analysis based on a single case study. These methods are: scenario analysis, decision trees, Monte-Carlo simulation modelling and discrete event simulation modelling. Our aims are, on the one hand, to guide the analyst through the modelling processes and, on the other hand, to demonstrate what additional decision support information can be obtained from applying each of these modelling methods.